2019
DOI: 10.1111/infa.12308
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world scene perception in infants: What factors guide attention allocation?

Abstract: The foci of visual attention were modeled as a function of perceptual salience, adult fixation locations, and attentional control mechanisms (measured in separate tasks) in infants (N = 45, 3‐ to 15‐month‐olds) as they viewed static real‐world scenes. After controlling for the center bias, the results showed that low‐level perceptual salience predicts where infants look. In addition, high‐level factors also played a role: Infants fixated parts of the scenes frequently fixated by adults and this effect was stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 92 publications
(147 reference statements)
1
25
1
Order By: Relevance
“…In contrast, Mills et al (2011) did find evidence for task-dependent changes in mean fixation duration and mean saccade amplitude when participants engaged in memorization, aesthetic judgment, free-viewing, and search tasks. Mills et al (2011) also found task-dependent differences in the rate of change in fixation duration over the course of a trial (see also, Antes, 1974;Friedman and Liebelt, 1981;Unema et al, 2005;Nuthmann et al, 2010;Nuthmann, 2017), while Castelhano et al (2009) found no effect of task on ordinal fixation duration. Several major differences between these studies may have contributed to their different findings.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, Mills et al (2011) did find evidence for task-dependent changes in mean fixation duration and mean saccade amplitude when participants engaged in memorization, aesthetic judgment, free-viewing, and search tasks. Mills et al (2011) also found task-dependent differences in the rate of change in fixation duration over the course of a trial (see also, Antes, 1974;Friedman and Liebelt, 1981;Unema et al, 2005;Nuthmann et al, 2010;Nuthmann, 2017), while Castelhano et al (2009) found no effect of task on ordinal fixation duration. Several major differences between these studies may have contributed to their different findings.…”
Section: Introductionmentioning
confidence: 94%
“…Cognitive psychologists use these measures to study perception (e.g., Currie et al, 2000;Gajewski and Henderson, 2005;Rayner et al, 2009;Smith et al, 2012), attention (e.g., Brockmole and Henderson, 2005a,b;Brockmole and Võ, 2010;Wolfe et al, 2011a,b;Hayes, 2017, 2018;Peacock et al, 2019) memory processes (e.g., Irwin and Zelinsky, 2002;Castelhano and Henderson, 2005;Hannula et al, 2012;Wolfe, 2012, 2013;Olejarczyk et al, 2014;Ramey et al, 2019), and language (e.g., Henderson and Ferreira, 2004;Kamide, 2007, 2009;, among other topics. Measures of eye movements in scenes are used in social psychology (Chua et al, 2005;Birmingham et al, 2008;Risko et al, 2012), clinical psychology (Fletcher-Watson et al, 2009;Hayes and Henderson, 2018;Tseng et al, 2013), and developmental psychology (Açik et al, 2010;Koski et al, 2013;Amso et al, 2014;Helo et al, 2014;van Renswoude et al, 2019). Human eye movements in scenes are also used to validate models of computer vision in engineering and computer science applications (Ehinger et al, 2009;Subramanian et al, 2011;Bylinskii et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that some of the differences that we found in infants' visual exploration behaviours between expressions may be driven by low-level visual features of the body images Frank et al, 2009;van Renswoude et al, 2019;Amso et al, 2014;Kwon et al, 2016;Itti et al, 1998;Itti & Koch, 2001). Previous studies have attempted to control for this by various stimulus manipulations, such as stimulus inversion in the picture plane.…”
Section: Discussionmentioning
confidence: 89%
“…Cognitive psychologists use these measures to study perception (e.g., Currie, McConkie, Carlson-Radvansky, & Irwin, 2000;Gajewski & Henderson, 2005;Rayner, Smith, Malcolm, & Henderson, 2009;Smith, Lamont, & Henderson, 2012), attention (e.g., Brockmole & Henderson, 2005a, b;Brockmole & Võ, 2010;Henderson & Hayes, 2017Peacock, Hayes, & Henderson, 2019;Wolfe, Võ, Evans, & Greene, 2011;Wolfe, Alvarez, Rosenholtz, Kuzmova, & Sherman, 2011) memory processes (e.g., Castelhano & Henderson, 2005;Hannula, Baym, Warren, & Cohen, 2012;Irwin & Zelinksy, 2002;Olejarczyk, Luke, & Henderson, 2014;Ramey, Yonelinas, & Henderson, 2019;Võ & Wolfe, 2012, and language (e.g., Altmann & Kamide, 2007, 2009Henderson & Ferreira, 2004;Henderson, Hayes, Rehrig, & Ferreira, 2018), among other topics. Measures of eye movements in scenes are used in social psychology (Birmingham, Bischof, & Kingstone, 2008;Chua, Boland, & Nisbett, 2005;Risko, Anderson, Lanthier, & Kingstone, 2012), clinical psychology (Fletcher-Watson, Leekam, Benson, Frank, & Findlay, 2009;Tseng, et al, 2013), and developmental psychology (Açik, Sarwary, Schultze-Kraft, Onat, & König, 2010;Amso, Haas, & Markant, 2014;Helo, Pannasch, Sirri, & Rӓmӓ, 2014;van Renswoude, Visser, Raijmakers, Tsang, & Johnson, 2019). Human eye movements in scenes are also used to validate models of computer vision in engineering and computer science applications (Bylinskii, PREPRINT: This manuscript is currently under peer review.…”
Section: Eye Movement Behavior In Scenesmentioning
confidence: 99%